Asymptotic Error Expansion and Defect Correction for Sobolev and Viscoelasticity Type Equations (Journal of Computational Mathematics, 1998)
In this paper we study the higher accuracy methods $-$ the extrapolation and defect correction for the semidiscrete Galerkin approximations to the solutions of Sobolev and viscoelasticity type equations. The global extrapolation and the correction approximations of third order, rather than the pointwise extrapolation results are presented.